Rewards and frustrations of being a social worker: a qualitative study. - Françozo MFC; Cassorla RMS (Journal of Social Work Practice, 2004)
This paper deals with aspects of actual professional experience of social workers, in order to grasp a framework for professional rewards and frustrations. A qualitative research tool was chosen, life histories, and ten social workers were interviewed. The subjects were women who graduated between the 1950s and the 1990s from schools of social work in Brazil, and whose practice, present or past, involves direct contact with clients. The reasons explaining satisfying professional situations are rooted in professional experiences which were translated into personal development, the establishment of personal ties and the acquisition of skills. Perceptions of having contributed towards solving a difficult situation and recognition from their clients were positively appraised. These are rewarding situations from which social workers derive the feeling of having created something which is positive for the clients and for themselves. Unpleasant situations were described as unfair situations experienced by clients, poor working conditions and difficulties concerning inter-professional relationships. Inferences on the feminine role as influencing social workers' rewards and frustrations with the profession, as well as inferences on possible unconscious configurations underlying some of the data were drawn in the conclusions.